Yield And Water Use Of Almond Under Drip Irrigation (Applied Biological Research, 2012)
An experiment was conducted at Central Institute of Temperate  Horticulture, Srinagar, Kashmir on almond (Prunus dulcis Mill.) cv.  ‘Shalimar’ plantation to standardize the water requirement for yield  optimization in almond. The study revealed that vegetatively propagated  almond plants positively responded to irrigation. The irrigation, applied  according to different ETc levels, improved yield and yield contributing  attributes of almond significantly. Highest nut yield (2.42 kg tree-1) was  recorded at 100% ETc during 1st year of experimentation which increased  to 2.91 kg tree-1in the subsequent year. Similarly, highest shelling  percentage (53%) was recorded in nuts receiving full irrigation during the 2nd year of experimentation. The highest yield and yield contributing  attributes of almond, recorded at 100% ETc level of irrigation, were  statistically at par with measured parameters recorded at 75% ETc level of  irrigation.
Keywords: Almond; evapotranspiration; micro-irrigation; Prunus dulcis; water requirement; yield